Increased monocyte tissue factor expression in coronary disease. - Leatham, E. W. (1995)
OBJECTIVE--To investigate whether monocyte expression of tissue factor is increased in patients with acute coronary syndromes and chronic stable angina. DESIGN--Cross sectional study of monocyte tissue factor expression in patients with ischaemic heart disease and control subjects. BACKGROUND--Unstable angina and myocardial infarction are associated with enhanced mononuclear cell procoagulant activity. Procoagulant activity of blood monocytes is principally mediated by tissue factor expression. Tissue factor initiates the coagulation cascade and monocyte tissue factor expression may therefore be increased in these syndromes. METHODS--Monocyte tissue factor expression was measured cytometrically in whole blood flow using a polyclonal rabbit antihuman tissue factor antibody. PATIENTS--30 patients with acute myocardial infarction, 17 with unstable angina, 13 with chronic stable angina, and 11 normal control subjects. RESULTS--Increased proportions of monocytes expressing tissue factor (> 2.5%) were found in none of 11 (0%) normal subjects, five 13 (38%) patients with stable angina, 11 of 17 (64%) patients with unstable angina, and 16 of 30 (53%) patients with myocardial infarction (2P = 0.006). Blood from all subjects showed similar monocyte tissue factor expression similar monocyte tissue factor expression (46.1 (15.1)%) after lipopolysaccharide stimulation. CONCLUSION--Hypercoagulability associated with acute myocardial infarction, unstable angina, and chronic stable angina may be induced by tissue factor expressed on circulating monocytes.